Characterisation of de-structured starch and its shear-thickening mechanism. (November 2022) - Ang, Cai Ling; Matia-Merino, Lara; Sims, Ian M.; Sargison, Liam; Edwards, Patrick J.B.; Lim, Kaiyang; Goh, Kelvin Kim Tha
Abstract: This study focuses on the relationship between the starch de-structuring process and its shear-induced rheological properties. Waxy potato starch underwent a de-structuring process (120–150 °C for 30 min under continuous stirring) where the starch granules were completely gelatinised and subsequently reduced into fragments and polymer chains. A significant increase in the degree of branching was noted in 140 and 150 °C de-structured waxy potato starch (DWPS) samples as compared to its native form. However, no significant change in the side-chain profile of DWPS samples was detected. Laser diffraction measurements revealed the presence of large particles in DWPS samples, which indicated that the starch de-structuring process into its macromolecules was incomplete even at 150 °C for 30 min. Complex shear-induced behaviours (shear-thickening, shear-induced gelation and/or anti-thixotropy) were noted in 120 and 140 °C DWPS samples. Such behaviours were attributed to the reduction in size and increased number of fragments, together with interactions among fragments and amylopectin chains in these DWPS samples when subjected to shear. Graphical abstract: Image 1 Highlights: Amylopectin chains were cleaved close to their center during de-structuring. De-structuring treatment resulted in a gradual increase in degree of branching. De-structuring treatment did not affect the starch side-chain profile. De-structuring process was incomplete even at 150 °C. Size of starch fragments contributed to shear-induced rheological properties.